Prevalence of co-trimoxazole resistance among HIV-infected individuals in Ethiopia: a systematic review and meta-analysis - Assefa, Muluneh; Girmay, Getu (Frontiers in Medicine, 2024)
Background Co-trimoxazole is used as a prophylaxis for human immunodeficiency virus (HIV) patients to prevent opportunistic infections. Its widespread use results in the emergence of co-trimoxazole resistance, which is a significant problem. This systematic review and meta-analysis determined the pooled prevalence of co-trimoxazole resistance among HIV-infected individuals in Ethiopia. Methods The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guideline was applied to report this study. The protocol has been registered in the International Prospective Register of Systematic Reviews (PROSPERO) under the assigned number CRD42024532240. Article search was performed using electronic databases such as PubMed, Medline, EMBASE, Google Scholar, Hinari, Web of Science, Science Direct, and African Journals Online. Data were extracted using a Microsoft Excel spreadsheet and analyzed using STATA version 11.0 software. A random-effects model was used to estimate the pooled effect size of co-trimoxazole resistance across studies with a 95% confidence interval. The heterogeneity was checked using I2 statistic. The presence of publication bias was determined using a funnel plot and Egger’s test with a p-value <0.05 evidence of statistically significant bias. Subgroup and sensitivity analyses were performed. Results Twenty-two studies with 5,788 HIV-infected individuals were included. The pooled prevalence of co-trimoxazole resistance was 61.73% (95% CI: 53.10–70.37%), with heterogeneity (I2 = 87.7%) and statistical significance (p < 0.001). A higher co-trimoxazole resistance was observed in HIV-infected individuals with urinary tract infection; 82.10% (95% CI: 75.03–89.17%). Among the bacterial spp., higher resistance to co-trimoxazole was observed in Escherichia coli; 70.86% (95% CI: 53.44–88.27%) followed by Salmonella spp.; 67.66% (95% CI: 41.51–93.81%) and Proteus spp.; 66.23% (95% CI: 34.65–97.82%). Conclusion There is a higher prevalence of co-trimoxazole resistance in HIV-infected individuals in Ethiopia. This alarms WHO’s recommendation of co-trimoxazole prophylaxis guidelines to review and update it. Additionally, a nationwide assessment of co-trimoxazole resistance in Ethiopia as a whole is required. Systematic review registration: identifier: CRD42024532240.